Sexual violence by juveniles in institutions: a descriptive study on prevalence and circumstances - Allroggen, Marc (International journal of offender therapy and comparative criminology, 2018)
Adolescents in institutionalized care are at a particularly high risk of exhibiting sexually aggressive behavior including sexual harassment. So far, however, studies about the prevalence of sexually aggressive behavior in institutions are lacking. In this survey, 322 adolescents (43% female, average age 16.7 years) from 32 residential care facilities and boarding schools across Germany were asked about sexually aggressive behavior via a standardized questionnaire. Overall, 23.5% of the participants engaged in some form of sexually aggressive behavior in their lives, and 4.6% reported having committed a sexual assault with (actual or attempted) penetration. A closer look at the circumstances of those offenses shows that the victims were in most cases acquainted with and of the same age as the offenders, that threats and violence were used in some cases, and especially in the case of actual or attempted penetration, and that only a minority of offenders suffered any consequences for their acts. The implementation of protective measures for institutions and the treatment of adolescents in institutions will be discussed.